ΣΥΓΧΡΟΝΗ ΜΟΥΣΙΚΗ ΣΤΟ ΑΝΑΒΙΩΜΕΝΟ ΑΡΧΑΙΟ ΔΡΑΜΑ. ΠΕΡΙΠΤΩΣΕΙΣ ΜΕΛΕΤΗΣ: Η ΜΟΥΣΙΚΗ ΤΟΥ ΓΙΑΝΝΗ ΧΡΗΣΤΟΥ ΓΙΑ ΤΟΥΣ ΠΕΡΣΕΣ ΤΟΥ ΑΙΣΧΥΛΟΥ (1965) ΚΑΙ ΤΟΥ ΚΩΝΣΤΑΝΤΙΝΟΥ ΒΗΤΑ ΓΙΑ ΤΗΝ ΙΦΙΓΕΝΕΙΑ ΕΝ ΑΥΛΙΔΙ ΤΟΥ ΕΥΡΙΠΙΔΗ (2012) [CONTEMPORARY MUSIC IN THE REVIVED ANCIENT DRAMA. CASE STUDIES: THE MUSIC FOR AESCHYLUS’ PERSIANS (1965) BY YIANNIS CHRISTOU AND THE MUSIC FOR EURIPIDES’ IPHIGENEIA IN AULIS BY KONSTANTINOS VETA (2012)] - Dalianoudi, Renata (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
The performances of the Αncient Greek Drama in the modern era are in fact a «partnership» of different, autonomous performing arts, through which the Ancient Drama is revived and reconstructed. In the context of multi-factorial performances, with clear specializations for music, dance, text, direction, set design, costumes, etc., the space-time is almost always intertwined with an incongruity with respect to time authorship of the work, its plot and the composer himself. The historical review of the most important ideological trends by directors, composers, art & music critics for the interpretation of Ancient Drama in the 20th century, reveal the ideological divergences and convergences regarding the role of music in revived ancient dramas in relation to tradition (folk song and byzantine chant) and its connection with antiquity. Cases study are the «expanded» music by Yiannis Christou for Aeschylus’ Persians (directed by Koun, 1965), and the electro-acoustic music by Konstantinos Veta for Euripides’ Iphigeneia in Aulis (directed by Moumoulidis, 2012), about which the author lays down new interpretative tools for the analysis of stage music in revived ancient dramas. The paper is based on archival and ethnographic research (in situ and with interviews of contributors) and on the interdisciplinary approach of music from the disciplines of (ethno)musicology, archaeo-musicology, theatrology.